Cerita â€œHibatâ€ Karangan R.H. Moehamad Meosa sebagai Embrio Cerita Pendek Sunda dalam Wacana Kolonialisme Abad ke-19 - Darpan, Darpan (UPI, 2019)
The research is based on the assumption that literary works written in the second half of the 19th century were the result of the efforts of the Dutch colonial government to incorporate the ideology of colonialism in culture field, and tried to instill modern ideas from the West through literacy activities. Some of these texts are stories written in short prose that are realistic. The story of